(untitled) - Trudeau, Noah Andre (New York, 2002)
America's Civil War raged for more than four years, the three days of fighting in the Pennsylvania countryside in July 1863 continue to fascinate, appall, and inspire new generations with their unparalleled saga of sacrifice and courage. No battle was as deadly or dramatic as Gettysburg. More lives were lost there than in any other war fought on American soil. From Chancellorsville, where General Robert E. Lee launched his high-risk campaign into the North, to the Confederates' last daring and ultimately doomed act, forever known as Pickett's Charge, the battle of Gettysburg gave the Union army a victory that turned back the boldest and perhaps greatest chance for a Southern nation. The last three decades have seen scores of remarkable new studies focusing on important elements of this monumental campaign. Now, acclaimed historian Noah Andre Trudeau brings the most up-to-date research available to a brilliant, sweeping, and comprehensive history that sheds new light on virtually every aspect of the battle of Gettysburg. Deftly balancing his own narrative style with revealing firsthand accounts, including excerpts from the diaries and letters of the men on both sides of the battlefield, Trudeau brings this engrossing human tale to life. He recounts the heightening tension of the campaign, the life-or-death decisions made by its commanders, and the struggle endured by thousands of its bravest soldiers. Not forgotten are the stories of the noncombatants, the thousands of civilians whose placid lives were swept into the ferocious cauldron.
Keywords: Gettysburg, Battle of, Gettysburg, Pa., 1863.,Mặt trận Gettysburg